Rediscovery of Argyreia coonoorensis Smith & Ramas. (Convolvulaceae) After a Century from The Nilgiris, Tamiil Nadu, India - Ramachandran, V. S.; Sasi, R. (Journal of the Bombay Natural History Society (JBNHS), 2012)
No Abstract.